Enhancement of amperometric response to tryptophan by proton relay effect of chitosan adsorbed on glassy carbon electrode - Paz Zanini, Veronica Irene (2014)
A simply prepared, low-cost, and sensitive electrochemically activated glassy carbon electrode (GCEa) modified with absorbed chitosan (CHIT) film for quantification of tryptophan (Trp) is reported. Combination of cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) techniques were used for characterization of the electro-oxidation of the amino acid and the electro-analytical performance of the CHIT-modified electrode. The electro-oxidation of Trp involves an irreversible two-electron and two-proton transfer process in both bare and modified electrodes, but the adsorption of CHIT as a polycation onto GCEa produces a ≈4-fold increase of the oxidation current of Trp without changing both the oxidation potential and the heterogeneous reaction rate constant, suggesting that the biopolymer behaves as a proton relay species, probably due to hydrogen bonding/proton acceptor capability of hydroxyl and ether groups of CHIT. Finally, the electro-analytical features of the CHIT-modified electrode as Trp sensor were also evaluated, obtaining a linear response range up to 130 μM Trp, sensitivity of 0.68 μA μM−1 and detection limit of 0.04 μM Trp, with almost no interference of other amino acids.